RESILIENCY PRACTICES IN EDUCATIONAL CRISIS MANAGEMENT AMONG SCHOOL ADMINISTRATORS - Pastor, Mark Joseph Deblois; Acosta, Rosabel Lorenzo; Aquino, Marlowe U (International Journal of Education, 2024)
The escalating impact of pandemics on schools, as exemplified by the pandemic crisis, underscores the pressing need for adept crisis management by school administrators. This study explores resiliency practices employed by public school administrators in the province of Ilocos Norte, Philippines, across three schools’ divisions before, during, and after the pandemic. Utilizing a phenomenological and narrative inquiry approach, themes emerged through categorization, analysis, and interpretation of data from documents and interviews. The findings underscore the importance of equipping school administrators with essential management tools such as capability-building initiatives, sustainability and contingency plans, as well as dynamic policies and guidelines. These elements collectively contribute to establishing resilience during pandemics. In response to these needs, the study introduces the Educational Crisis Resiliency Management Framework (ECRMF), a strategic educational management strategy validated for school administrators in Ilocos Norte. This framework serves as a comprehensive response to educational crisis, including pandemics, emphasizing the necessity of preparedness and effective crisis leadership. The ECRMF offers a valuable resource for school administrators navigating crises, emphasizing the importance of proactive measures and strategic procedures. As a conclusion, the study recommends further research to investigate additional practices of school administrators, providing a more in-depth exploration of disaster management in the educational realm.